The Role of Malic Enzyme on Promoting Total Lipid and Fatty Acid Production in Phaeodactylum tricornutum - Zhu, Bao-Hua; Zhang, Rui-Hao; Lv, Na-Na; Yang, Guan-Pin; Wang, Yi-Sheng; Pan, Ke-Hou (Frontiers in Plant Science, 2018)
To verify the function of malic enzyme (ME1), the ME1 gene was endogenously overexpressed in Phaeodactylum tricornutum. Overexpression of ME1 increased neutral and total lipid content and significantly increased saturated fatty acids (SFAs) and polyunsaturated fatty acids (PUFAs) in transformants, which varied between 23.19% and 25.32% in SFAs and between 49.02% and 54.04% in PUFAs, respectively. Additionally, increased ME1 activity was accompanied by elevated NADPH content in all three transformants, indicating that increased ME1 activity produced additional NADPH comparing with that of WT. These results indicated that ME1 activity is NADP-dependent and plays an important role in the NADPH levels required for lipid synthesis and fatty acid desaturation in P. tricornutum. Furthermore, our findings suggested that overexpression of endogenous ME1 represents a valid method for boosting neutral-lipid yield in diatom.